2016
DOI: 10.1155/2016/8473937
|View full text |Cite
|
Sign up to set email alerts
|

Bee Pollen as a Promising Agent in the Burn Wounds Treatment

Abstract: The aim of the present study was to visualize the benefits and advantages derived from preparations based on extracts of bee pollen as compared to pharmaceuticals commonly used in the treatment of burns. The bee pollen ointment was applied for the first time in topical burn treatment. Experimental burn wounds were inflicted on two white, domestic pigs. Clinical, histopathological, and microbiological assessment of specimens from burn wounds, inflicted on polish domestic pigs, treated with silver sulfadiazine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…However, the observed results generally confirm high anti-staphylococcal potential of BP and particularly BB extracts and additionally support the need for more advanced studies focusing on the application of these products for treatment of bacterial infections. Moreover, Olczyk and coworkers revealed that bee pollen ointment may affect the wound healing process of burn wounds, preventing infection of the newly formed tissue [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed results generally confirm high anti-staphylococcal potential of BP and particularly BB extracts and additionally support the need for more advanced studies focusing on the application of these products for treatment of bacterial infections. Moreover, Olczyk and coworkers revealed that bee pollen ointment may affect the wound healing process of burn wounds, preventing infection of the newly formed tissue [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus) (Dustmann, 1979;Maeda et al, 2008) as well as anti-inflammatory (reviewed in Hadagali and Chua, 2014). Bee pollen has been described mostly as a nutraceutical, but has also been shown to exhibit pro-regenerative properties in burn wounds in pre-clinical experiments (Olczyk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It also has a positive effect on the skin by reducing water loss and influencing the lipid barrier. Bee pollen is also used to treat skin burns due to the high content of biologically active substances [ 29 ].…”
Section: Products Of Bee Origin—effect On Human Health Its Various Applications and A Source Of Chemical Contaminantsmentioning
confidence: 99%